Quadrotor Proportional-Derivative Regulation for onzero Set Point on SO(3) with Disturbance Compensation - S Herdjunanto; A P Sandiwan; A I Cahyadi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
Disturbance compensation is a challenging problem in quadrotor control, especially in nonzero set point regulation. This paper presents proportional-derivative regulation for nonzero set point on SO(3) with disturbance compensation for quadrotor UAV. Quadrotor nonlinear kinematics and dynamics model in SO(3) are used to design the control law. Disturbance compensation is added to the control law by using the upper bound of the disturbance. The numerical simulation shows that the disturbance compensation is able to counter the disturbance effect and improve the bound of the state variables.